A Systematic Design towards Usability for Novice Designers - Hoo Meei Hao; Azizah Jaafar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Dependence on intuitive and experiences would add more complexity in the design process. Novice designers would follow the design of any existing systems without direction. This paper proposed a systematic design approach that provides guidance for novice designers in achieving the targeted usability goal using patterns, and evaluating the prototypes in achieving the determined usability goals. The proposed approach involved the cooperation of experts in providing direction to the novice designers in achieving usability goal in the system design. A collective decision both from users and experts would be gather to give a clear decision of a chosen prototype. Two experiments that followed the proposed approach were conducted with 7 groups or 33 undergraduate students. Ten industry experts, 10 field experts and 29 prospective users were involved in evaluating the appropriate use of the tool to assist them in making decision during comparative prototype evaluation. The result from both experiments concluded the systematic approach could help the novice designers to emphasize usability along the design process. It was observed that the achievement of important goals in their designed prototype could be easily done if pattern selection was provided to the novice designers. The designed tool to assist novice designers has high reliability and high acceptance level of appropriate of use in making decision for the preferred prototype.